Details of bioecology of eggs of Trichocephalus spp. on pasture in conditions of eastern part of Сentral Сaucasus - Z. T. Baysarova (Российский паразитологический журнал, 2016)
Terms of development of embryonated eggs of Trichocephalus spp. and their viability on pasture in conditions of Eastern part of Central Caucasus are studied. The contamination of environment with eggs of Trichocephalus spp. has been de- fined by examination of 1143 fecal specimen obtained from soil on pastures and in lambing barns. Fecal specimens were examined using a floatation method. Besides the percentage of infection in specimens and the amount of eggs of Trichocephalus spp. in 1 g of fecal specimen obtained from soil are indentified. The maximum con- tamination of environment with eggs of Trichocephalus spp. is reported in autumn due to accumulation and preservation of embryonated eggs. The analyze of 1 kg of faeces (22,3±3,4 - 47,4±5,2 expl. eggs of Trichocephalus spp.) allows to conclude that the contamination of fecal specimen obtained from grazing areas makes 13,0 %, from pasture - 6,6%, from farm territories - 10,5 %. In spring the minimum en- vironmental contamination was reported due to elimination of a big amount of eggs in winter. Development of embryonated eggs of Trichocephalus spp. on pasture occurs within 46 days in April, within 22 days in June and within 51 days in Octo- ber. In various months the different amount of embryonated eggs in fecal specimen obtained from pasture is determined. Therefore in April, June and September the amount of viable eggs makes 24,0; 55,3 and 74,3 %. Keywords: eggs, Trichocephalus spp., viability, contamination, terms of de- velopment, pasture, Chechen Republic.